# Cosh(2x-1)=0

## Simple and best practice solution for Cosh(2x-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for Cosh(2x-1)=0 equation:

Simplifying
Cosh(2x + -1) = 0
Reorder the terms:
hosC(-1 + 2x) = 0
(-1 * hosC + 2x * hosC) = 0
(-1hosC + 2hosxC) = 0
Solving
-1hosC + 2hosxC = 0
Solving for variable 'h'.
Move all terms containing h to the left, all other terms to the right.
Factor out the Greatest Common Factor (GCF), 'hosC'.
hosC(-1 + 2x) = 0
Subproblem 1Set the factor 'hosC' equal to zero and attempt to solve:
Simplifying
hosC = 0
Solving
hosC = 0
Move all terms containing h to the left, all other terms to the right.
Simplifying
hosC = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1 + 2x)' equal to zero and attempt to solve:
Simplifying
-1 + 2x = 0
Solving
-1 + 2x = 0
Move all terms containing h to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + 2x = 0 + 1
Combine like terms: -1 + 1 = 0
0 + 2x = 0 + 1
2x = 0 + 1
Combine like terms: 0 + 1 = 1
2x = 1
Add '-2x' to each side of the equation.
2x + -2x = 1 + -2x
Combine like terms: 2x + -2x = 0
0 = 1 + -2x
Simplifying
0 = 1 + -2x
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`